VGM business portraits Coca-Cola - Gould, William 1947- (Lincolnwood, Ill. VGM Career Horizons, 1995)
An introduction to basic business concepts, using the Coca-Cola Company as a case study.
Keywords: Coca-Cola Company -- Juvenile literature; Coca-Cola Company; Soft drink industry -- United States -- Juvenile literature; Soft drink industry